1993
DOI: 10.1002/clc.4960160514
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol‐induced myocardial ischemia: Close relation between blood acetaldehyde level and myocardial ischemia

Abstract: Summary:A patient with vasospastic angina who developed myocardial ischemia following ethanol ingestion but not after exercise was described. Myocardial ischemia was evidenced by electrocardiograms (ECGs) and thallium-20 1 scintigrams. The blood acetaldehyde level after ethanol ingestion was abnormally high. The time course and severity of myocardial ischemia coincided with those of the blood ethanol and acetaldehyde level. Coronary arteriography showed ergonovine maleate-induced coronary vasospasm at the left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…While the levels of acetaldehyde in normal subjects are 0.2-5 μM, after ingestion of alcohol or in subjects with liver disease the level is increased 3-30 fold [51]. The salivary acetaldehyde levels of smoking and drinking subjects are quite high with values of 370 μM reported [52].…”
Section: Discussionmentioning
confidence: 99%
“…While the levels of acetaldehyde in normal subjects are 0.2-5 μM, after ingestion of alcohol or in subjects with liver disease the level is increased 3-30 fold [51]. The salivary acetaldehyde levels of smoking and drinking subjects are quite high with values of 370 μM reported [52].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that acetaldehyde may be instrumental in inducing myocardial ischemia and coronary vasospasm (assessed by both ECG and thallium 201 scintograms) after alcohol consumption (68). The abnormalities were not perturbed by treadmill exercise alone (68). Studies with troponin-T in the rat (described below) support a mechanism involving ischemia.…”
Section: Alcohol and Cardiac Ischemic Damagementioning
confidence: 98%
“…Thus it is not unreasonable to propose mechanisms involving ischemic heart muscle damage in the aetiology of alcoholic heart muscle disease and if this occurs, then a re-perfusion type injury will also ensue. It has been suggested that acetaldehyde may be instrumental in inducing myocardial ischemia and coronary vasospasm (assessed by both ECG and thallium 201 scintograms) after alcohol consumption (68). The abnormalities were not perturbed by treadmill exercise alone (68).…”
Section: Alcohol and Cardiac Ischemic Damagementioning
confidence: 99%
“…Increased blood AcH level might be responsible for the development of coronary vasospasm and myocardial ischemia [4][5][6]. We suspected according to our patient_s description and clinical presentation that disulfiramalcohol interaction might be a causative mechanism for developing myocardial infarction because of the close temporal relationship between those two events.…”
mentioning
confidence: 92%